Continuous performance test in pediatric obsessive-compulsive disorder and tic disorders: the role of sustained attention. (9th October 2014) - Lucke, Ilse M.; Lin, Charlotte; Conteh, Fatmata; Federline, Amanda; Sung, Huyngmo; Specht, Matthew; Grados, Marco A.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Pediatric obsessive-compulsive disorder (OCD) and tic disorders (TD) are often associated with attention-deficit hyperactivity disorder (ADHD). In order to clarify the role of attention and inhibitory control in pediatric OCD and TD, a continuous performance test (CPT) was administered to a cohort of children and adolescents with OCD alone, TD alone, and OCD+TD. Methods A clinical cohort of 48 children and adolescents with OCD alone (n=20), TD alone (n=15), or OCD+TD (n=13) was interviewed clinically and administered the Conners Continuous Performance Test II (CPT-II). The Conners CPT-II is a 14-minute normed computerized test consisting of 6 blocks. It taps into attention, inhibitory control, and sustained attention cognitive domains. Key parameters include errors of omission (distractability), commission (inhibitory control), and variable responding over time (sustained attention). Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) criteria were applied in a best-estimate process to diagnose OCD, TD, ADHD, and anxiety disorders. Results Children with OCD+TD had more errors of omission (p=0.03), and more hit RT block change (p=0.003) and hit SE block change (p=0.02) than subjects with OCD alone and TD alone. These deficits in sustained attention were associated with younger age and hoarding tendencies. A clinical diagnosis of ADHD in the OCD+TD group also determined worse sustained attention. Conclusions A deficit in sustained attention, a core marker of ADHD, is also a marker of OCD+TD, compared to OCD alone and TD alone. Biological correlates of sustained attention may serve to uncover the pathophysiology of OCD and TD through genetic and imaging studies.